Peran Negara dalam Hisbah - Mujahidin, Akhmad (Al-Iqtishad: Journal of Islamic Economics, 2012)
This article is a review of the theoretical hisbah authority and how the State has a role in it. The most important role of the State in the implementation of technically hisbah that mustahib task is holding the governor of executive power, legal power of the disctrict court, as well as regional policy powers. Muhtasib have a responsibility for the welafe of Islamic society. Islam concerns in world and hereafter to build human welfare. Therefore, muhtasib jurisdiction is not limited. Muhtasib attention is on what is specified by Allah and all that is legally recognized as a man desires.DOI: 10.15408/aiq.v4i1.2094